[Cellular mechanisms of regulation of the inflammatory response in atherosclerosis: the role of cell contact-mediated signaling] - Monaco, C; Young, S; Paleolog, E; Maseri, A; Feldmann, M (2001)
The regulatory mechanisms of the inflammatory process in the atherosclerotic plaque are still not clearly understood. Stimulated T cells may have a key role in enhancing and perpetuating inflammation at the atherosclerotic site. They activate endothelial cells, macrophages and smooth muscle cells in the atherosclerotic plaque, not only via the production of soluble mediators, but also through cell-cell contact-mediated interactions (via membrane receptors and their ligands). Cell/cell contact between stimulated T lymphocytes and monocytes/macrophages and endothelial cells induces the production of pro-inflammatory cytokines (tumor necrosis factor-alpha, interleukin-6) and chemokines (interleukin-8, monocyte chemotactic factor-1). Thus, these interactions could play a relevant role in the disregulation of the inflammatory process in the atherosclerotic plaque, representing a novel mechanism of progression and complication of the atherosclerotic disease. Understanding the key ligands and receptors involved may permit the definition of new therapeutic targets.